Spatial distribution of various parameters in groundwater of Delhi, India. Issue 1 (31st December 2016) - Gupta, Parul; Sarma, Kiranmay
Abstract: The present study analyzed the spatial variability in groundwater quality and depth in National Capital Territory (NCT) of Delhi, India. The study classified the parameters into five distribution classes viz., low, moderately low, moderate, moderately high, and high. Spatial variability maps were generated using kriging tool in ArcGIS environment. Primary data collected seasonally during 2012–2014 were used for the generation of maps. Physico-chemical parameters were correlated with each other and groundwater depth. All the parameters were found to be negatively correlated with groundwater depth. Spatial distribution maps showed that maximum concentration of most parameters was found in the northern parts of the study area, while maximum depth was reported from the southern part. Maximum area of around 59% of total area of Delhi has low electrical conductivity, TDS, and hardness values. With groundwater depth improving toward north Delhi, groundwater quality is found to be improving toward south parts of Delhi.